Menggambar Kartun Tematik pada Guru-Guru PAUD/Taman Kanak-Kanak di Kota Makassar - Karta Jayadi; Arifin Manggau (DEDIKASI, 2019)
The purpose of this program is how kindergarten teachers can recognize, understand and be able to drawthematic cartoons. The identification of problems that are often encountered in kindergarten especially in MakassarCity is the lack of ability of kindergarten teachers in understanding and skillfully making thematic cartoons. Somerelated activities include: 1) Identification of thematic cartoons and their types for the kindergarten children categoryin Makassar City, 2) Introduction of thematic cartoons for teachers for kindergarten children in the form ofperformance, and, 3) The presentation form of the thematic cartoon which drew by teachers for kindergartenchildren. The results of this program, are: 1) The number of kindergarten teachers who have recognized andunderstood the types and forms of thematic cartoons for early childhood. There are funny cartoons, humorouscartoons, as well as criticism cartoons, 2) The teacher has been able to know the technique of drawing thematiccartoons in the form of performance. It has produced cartoons from funny pictures to critical ones. 3) The teacher isskilled at presenting thematic cartoons in a simple way.